PARKINSON’S DISEASE IN DENTISTRY AND PERIODONTOLOGY - Zeliha Muslu; Hakan Develioğlu (Cumhuriyet Dental Journal, 2017)
Parkinson’s disease (PD) is a progressive neurological condition which is characterised by motor (movement) and non-motor symptoms. The disorder is characterized by hypokinesia, tremor, muscular rigidity, and a shuffling gait. Oral hygiene procedures may be adversely affected by tremor, disturbance of motor skills and depression which are seen with these patients. It is also known that the medicines used in the treatment of the disease have various side effects that affect the oral area. It has been demonstrated in previous studies that the oral and dental health status of Parkinson's patients is worse than healthy individuals, and they have a larger number and more deep periodontal pockets. The purpose of this review is to compare the relationship between Parkinson's disease with dental and periodontal health and to compile up-to-date information by scanning the literature to better understand the possible mechanism.